The relationship between financial education and downstream financial health - Machiz, Ives Martin (Kansas State University, 2023)
Many Americans are in a precarious financial situation: living paycheck to paycheck, unable to fund relatively trivial unexpected expenses, and unable to save substantially for retirement and other financial goals. Low financial literacy has been cited as one of the leading causes of suboptimal economic outcomes. Financial illiteracy, meaning that an individual lacks the knowledge to know what a good financial decision is and/or belief that they can execute a good financial decision, is also a source of economic inequities among genders, ethnicities, and other marginalized communities. The consequence is that a significant portion of the US population is financially fragile and in danger of being unable to meet basic needs due to unemployment, medical issues, or other financial difficulties which may arise. This study considered financial education as a potential solution to this problem. Prior literature has indicated positive relationships between financial education and financial literacy, and between financial literacy and financial behaviors. However, there is little information on the relationship between financial education and economic endpoints. This study expanded on prior research by considering the chain of events from receiving financial education all the way through economic outcomes, using the Theory of Planned Behavior (TPB) as a scaffold. Using structural equation modeling (SEM), the study explored the complex set of factors which intervene between being exposed to financial education and economic outcomes which occur later. This study also integrated the concept of financial health as an analogue to physical health, measuring not just financial behaviors, but the economic results of those actions. The SEM analysis found a significant relationship between financial education and financial health, which was mediated by constructs in the TPB. Propensity score matching was also used to create an artificially randomized data set, to isolate the effects of financial education on financial outcomes more strictly. The matching homogenized the demographic differences between those who received financial education and those who did not. Regression and ANOVA analyses confirmed that a significant relationship between financial education and financial health existed. The relationship was significant whether financial education was measured as a binary variable, by level of education, or by number of exposures to financial education. The strongest positive effects of financial education were seen in the domain of positive financial outcomes, specifically asset accumulation. The evidence presented makes a strong case for financial education as an economically demonstrable solution to the problems brought on by low financial literacy. Certainly, financial education is not a standalone solution, but it can be a powerful part of a package of solutions to strengthen the financial circumstances of Americans.
Keywords: Financial education; Financial health; Financial literacy